TLR2 Regulates Mast Cell IL-6 and IL-13 Production During Listeria monocytogenes Infection - Soria-Castro, Rodolfo; Alfaro-Doblado, Ángel R.; Rodríguez-López, Gloria; Campillo-Navarro, Marcia; Meneses-Preza, Yatsiri G.; Galán-Salinas, Adrian; Alvarez-Jimenez, Violeta; Yam-Puc, Juan C.; Munguía-Fuentes, Rosario; Domínguez-Flores, Adriana; Estrada-Parra, Sergio; Pérez-Tapia, Sonia M.; et al. (Frontiers in Immunology, 2021)
Listeria monocytogenes (L.m) is efficiently controlled by several cells of the innate immunity, including the Mast Cell (MC). MC is activated by L.m inducing its degranulation, cytokine production and microbicidal mechanisms. TLR2 is required for the optimal control of L.m infection by different cells of the immune system. However, little is known about the MC receptors involved in recognizing this bacterium and whether these interactions mediate MC activation. In this study, we analyzed whether TLR2 is involved in mediating different MC activation responses during L.m infection. We found that despite MC were infected with L.m, they were able to clear the bacterial load. In addition, MC degranulated and produced ROS, TNF-α, IL-1β, IL-6, IL-13 and MCP-1 in response to bacterial infection. Interestingly, L.m induced the activation of signaling proteins: ERK, p38 and NF-κB. When TLR2 was blocked, L.m endocytosis, bactericidal activity, ROS production and mast cell degranulation were not affected. Interestingly, only IL-6 and IL-13 production were affected when TLR2 was inhibited in response to L.m infection. Furthermore, p38 activation depended on TLR2, but not ERK or NF-B activation. These results indicate that TLR2 mediates only some MC activation pathways during L.m infection, mainly those related to IL-6 and IL-13 production.